2016
DOI: 10.1149/2.0721613jes
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Surface Stress Response during Reversible Mg Electrodeposition and Stripping

Abstract: Through the use of in situ electrochemical surface stress measurements, Mg deposition and stripping processes in electrolytes for Mg batteries are studied. We examine four electrolytes: PhMgCl+AlCl 3 /THF, (DTBP)MgCl-MgCl 2 /THF, MgCl 2 +AlCl 3 /THF, and Mg(BH 4 ) 2 +LiBH 4 /diglyme. Each of these electrolytes exhibits common surface stress response features, indicating that the mechanisms of Mg deposition and stripping are similar among the different electrolytes. Combining the measurements with density funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…The reason for a change in peak shape can be understood from previous work studying the oxidative processes during stripping. Our group has shown with in situ electrochemical stress experiments coupled with density functional theory (DFT) calculations that the Mg stripping curve can be broken down into a few sequential oxidation processes . As oxidation begins on the positive CV sweep, the majority of the anodic processes involve oxidation of Mg(101̅0) planes to Mg 2+ or MgO x , followed by oxidation of Mg(0001) planes and removal of MgO x as evidenced by two distinct regions in the stress curve .…”
Section: Resultsmentioning
confidence: 99%
“…The reason for a change in peak shape can be understood from previous work studying the oxidative processes during stripping. Our group has shown with in situ electrochemical stress experiments coupled with density functional theory (DFT) calculations that the Mg stripping curve can be broken down into a few sequential oxidation processes . As oxidation begins on the positive CV sweep, the majority of the anodic processes involve oxidation of Mg(101̅0) planes to Mg 2+ or MgO x , followed by oxidation of Mg(0001) planes and removal of MgO x as evidenced by two distinct regions in the stress curve .…”
Section: Resultsmentioning
confidence: 99%
“…There are some interesting research directions that can be taken in future studies. In addition to considering polyethylene oxide as discussed above, the use of LiBH 4 as a coelectrolyte to Mg(BH 4 ) 2 24,25,55 could be an interesting topic. In this work, we have approximated the liquid using a continuum solvation method using the static and dynamic dielectric constants of each solvent in its pure form without any dissolved ions.…”
Section: Discussionmentioning
confidence: 99%
“…This marked the discovery of the first stable, halide-free electrolyte for magnesium batteries. Since then, there have been a number of experimental 13,[20][21][22][23][24][25] and theoretical 12,23,26 studies aimed at improving battery performance. Presently, there are some problems with this electrolyte, including low ionic conductivity and solubility.…”
mentioning
confidence: 99%
“…We previously suggested that Mg deposition from a series of electrolytes containing different salts proceeded according to a similar mechanism. 19 In certain cases, the presence of a Mg dimer [Mg 2 (μ-Cl) 3 •6THF] + was correlated with the advent of efficient Mg electrodeposition. 5,8,17,20,21 The monomeric complexes, (MgCl 2 •4THF) and (MgCl•5THF) + resulting from the original dimer, were suggested to be the intermediate species present at the interface.…”
Section: ■ Introductionmentioning
confidence: 99%